The Impact of State-Owned Hospital Consolidation on the Performance of Affiliated Hospitals: A Case Study of Krakatau Medika Hospital - Maysa Melda An’umillah (Syntax Corporation, 2023)
This study aims to investigate the effect of consolidation on the performance of Krakatau Medika Hospital below a group called Indonesia Healthcare Corporation (IHC). The concept of consolidation in the healthcare sector is the focus of the study due to the lack of research that examines this phenomenon in depth. The data used includes several hospital performance indicators, such as operational efficiency, service quality, finance, and other important aspects. By using Balance Scorecard and paired Friedman test, the study reveals that even though the score of performance from the Balance Scorecard gradually improved after the consolidation, the significance of the analyzed data is below 0.05, indicated that there are no remarkable impact of consolidation towards the hospital’s performance. It is advised to take more time to do in-depth research to see how the consolidation actually impacted the hospital.